FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN NON-KEUANGAN DI INDONESIA - Natasha Nasution; Suryanto (E-Jurnal Akuntansi TSM, 2022)
The purpose of this research is to analyze factors influencing firm value in non-financial companies in Indonesia. Those factors are managerial ownership, institutional ownership, capital structure, profitability, company growth, liquidity, firm size and dividend policy. Population of this research is non-financial companies listed in the Indonesia Stock Exchange from 2013 to 2016. Samples consist of 48 non-financial companies selected using purposive sampling method. Data were analyzed using multiple linear regression. The result of this research shows that managerial ownership, institutional ownership, profitability and company growth have influence on firm value. Whereas, capital structure, liquidity, firm size and dividend policy do not have influence on firm value.